Recursive Evaluation of Fault Tolerance Mechanisms for SLA Management - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Proceedings of the 1. GI/ITG KuVS Fachgespräch Virtualisierung

Storage Cluster Architectures - Brinkmann, André; Effert, Sascha (Proc. of the GI/ITG KuVS Fachgespr ̈ach Virtualisierung)

Guiding exploration by combining individual learning and imitation in societies of autonomous robots - Richert, Willi; Klompmaker, Florian; Niehörster, Oliver (Proc. IFIP Conf. on Biologically Inspired Cooperative Computing (BICC))

GPU-Supported Image Compression for Remote Visualization - Realization and Benchmarking - Lietsch, Stefan; Hermann Lensing, Paul (Proc. Int. Symp. on Visual Computing (ISVC))

Computational Steering verteilter, interaktiver Materialflusssimulationen - Laroque, Christoph; Lietsch, Stefan; Zabel, Henning (Augmented & Virtual Reality in der Produktentstehung)

Degree 3 Suffices: A Large-Scale Overlay for P2P Networks - Bienkowski, Marcin; Brinkmann, André; Korzeniowski, Miroslaw (Proc. Int. Conf. on Principles Of DIstributed Systems (OPODIS))

Applying Risk Management to Support SLA Provisioning - Battre, Dominic; Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Cracow Grid Workshop (CGW))

Implementing WS-Agreement in a Globus Toolkit 4.0 Environment - Battré, Dominic; Kao, Odej; Voss, Kerstin (Proc. Usage of Service Level Agreements in Grids Workshop held in conjunction with International Conference on Grid Computing)

EvAnT: Analysis and Checking of event traces for Wireless Sensor Networks - Woehrle, Matthias; Plessl, Christian; Lim, Roman; Beutel, Jan; Thiele, Lothar (IEEE Int. Conf. on Sensor Networks, Ubiquitous, and Trustworthy Computing (SUTC))
Keywords: WSN; testing; verification

A Hardware Accelerator for k-th Nearest Neighbor Thinning - Schumacher, Tobias; Meiche, Robert; Kaufmann, Paul; Lübbers, Enno; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))

IMORC: An infrastructure for performance monitoring and optimization of reconfigurable computers - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Many-core and Reconfigurable Supercomputing Conference (MRSC))
Keywords: IMORC; IP core; interconnect

Planning-based Scheduling for SLA-awareness and Grid Integration - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Workshop of the UK PLANNING AND SCHEDULING Special Interest Group (PlanSIG))
Service level agreements (SLAs) are powerful instruments for describing all obligations and expectations in a business relationship. It is of focal importance for deploying Grid technology to commercial applications. The EC-funded project HPC4U (Highly Predictable Clusters for Internet Grids) aimed at introducing SLA-awareness in local resource management systems, while the EC-funded project AssessGrid introduced the notion of risk, which is associated with every business contract. This paper highlights the concept of planning based resource management and describes the SLA-aware scheduler developed and used in these projects.

Transparent Cross Border Migration of Parallel Multi Node Applications - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Cracow Grid Workshop, Academic Computer Center CYFRNET)

A CUDA-Supported Approach to Remote Rendering - Lietsch, Stefan; Marquardt, Oliver (Proc. Int. Symp. on Visual Computing (ISVC))

Comparing Fault Tolerance Mechanisms for Self-Organizing Resource Management in Grids - Voss, Kerstin (Proc. Int. Conf. on Semantics, Knowledge and Grid (SKG))

Gaining Users' Trust by Publishing Failure Probabilities - Battré, Dominic; Djemame, Karim; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on Security and Privacy in Communications Networks (SecureComm))

Increasing the Reliability of Wireless Sensor Networks with a Unit Testing Framework - Beutel, Jan; Plessl, Christian; Woehrle, Matthias

AssessGrid, Economic Issues Underlying Risk Awareness in Grids - Voss, Kerstin; Djemame, Karim; Gourlay, Iain; Padgett, James (Proc. Int. Worksh. on Grid Economics and Business Models (GECON))

Enhance Self-managing Grids by Risk Management - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Computational Steering of Interactive and Distributed Virtual Reality Applications - Lietsch, Stefan; Zabel, Henning; Berssenbruegge, Jan (Proc. ASME Computers and Information in Engineering Conference (CIE))

Gather and Prepare Monitoring Data for Estimating Resource Stability - Birkenheuer, Georg; Majlender, Peter; Nitsche, Holger; Voss, Kerstin; Weber, Elmar (Proc. Cracow Grid Workshop (CGW))

Verteilte Berechnung und Darstellung automobiler Scheinwerfer - Berssenbrügge, Jan; Lietsch, Stefan (Proc. Worksh. Augmented & Virtual Reality in der Produktentstehung)

Increasing the Reliability of Wireless Sensor Networks with a Distributed Testing Framework - Woehrle, Matthias; Plessl, Christian; Beutel, Jan; Thiele, Lothar (Proc. Workshop on Embedded Networked Sensors (EmNets))
Keywords: WSN; testing; distributed; embedded

Automated Wireless Sensor Network Testing - Beutel, Jan; Dyer, Matthias; Lim, Roman; Plessl, Christian; Woehrle, Matthias; Yuecel, Mustafa; Thiele, Lothar (Proc. Int. Conf. Networked Sensing Systems (INSS))
Keywords: WSN; testing; verification

Provision of Fault Tolerance with Grid-enabled and SLA-aware Resource Management Systems - Heine, Felix; Hovestadt, Matthias; Kao, Odej; Keller, Axel (Parallel Computing: Current and Future Issues of High End Computing)

The Virtual Resource Manager: Local Autonomy versus QoS Guarantees for Grid Applications - Burchard, Lars-Olof; Heine, Felix; Heiss, Hans-Ulrich; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry; Schneider, Jörg (Future Generation Grids)
In this paper, we describe the architecture of the virtual resource manager VRM, a management system designed to reside on top of local resource management systems for cluster computers and other kinds of resources. The most important feature of the VRM is its capability to handle quality-of-service (QoS) guarantees and service-level agreements (SLAs). The particular emphasis of the paper is on the various opportunities to deal with local autonomy for resource management systems not supporting SLAs. As local administrators may not want to hand over complete control to the Grid management, it is necessary to define strategies that deal with this issue. Local autonomy should be retained as much as possible while providing reliability and QoS guarantees for Grid applications, e.g., specified as SLAs.

Introducing Risk Management into the Grid - Djemame, Karim; Gourlay, Iain; Padgett, James; Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on e-Science and Grid Computing)

The First Step of Introducing Risk Management for Prepossessing SLAs - Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on Services Computing (SCC))

Reformulating XPath queries and XSLT queries on XSLT views - Groppe, Sven; Böttcher, Stefan; Birkenheuer, Georg; Höing, André (Data & Knowledge Engineering)

Risk Aware Migrations for Prepossessing SLAs - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Light Simulation in a Distributed Driving Simulator - Lietsch, Stefan; Zabel, Henning; Berssenbruegge, Jan; Wittenberg, Veit; Eikermann, Martin (Proc. Int. Symp. on Visual Computing (ISVC))

First Steps of a Monitoring Framework to Empower Risk Assessment on Grids - Lerch, Nicolas; Nitsche, Holger; Voss, Kerstin; Hovestadt, Matthias (Proc. Cracow Grid Workshop (CGW))

On Similarities of Grid Resources for Identifying Potential Migration Targets - Birkenheuer, Georg; Döhre, Sven; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Cracow Grid Workshop (CGW))

Using WS-Agreement for Risk Management in the Grid - Birkenheuer, Georg; Djemame, Karim; Gourlay, Iain; Kao, Odej; Padgett, James; Voß, Kerstin (Proc. WS-Agreement Workshop (Open Grid Forum 18))

SLA-aware Job Migration in Grid Environments - Heine, Felix; Hovestadt, Matthias; Kao, Odej; Keller, Axel (Grid Computing: New Frontiers of High Performance Computing)
Grid Computing promises an efficient sharing of world-wide distributed resources, ranging from hardware, software, expert knowledge to special I/O devices. However, although the main Grid mechanisms are already developed or are currently addressed by tremendous research effort, the Grid environment still suffers from a low acceptance in different user communities. Beside difficulties regarding an intuitive and comfortable resource access, various problems related to the reliability and the Quality-of-Service while using the Grid exist. Users should be able to rely, that their jobs will have certain priority at the remote Grid site and that they will be finished upon the agreed time regardless of any provider problems. Therefore, QoS issues have to be considered in the Grid middleware but also in the local resource management systems at the Grid sites. However, most of the currently used resource management systems are not suitable for SLAs, as they do not support resource reservation and do not offer mechanisms for job checkpointing/migration respectively. The latter are mandatory for Grid providers as rescue anchor in case of system failures or system overload. This paper focuses on SLA-aware job migration and presents a work, which is being performed in the EU supported project HPC4U.

A Quality-of-Service Architecture for Future Grid Computing Applications. - Burchard, Lars-Olof; Heine, Felix; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry (Proc. IEEE Int. Parallel & Distributed Processing Symposium (IPDPS))
The next generation grid applications demand grid middleware for a flexible negotiation mechanism supporting various ways of quality-of-service (QoS) guarantees. In this context, a QoS guarantee covers simultaneous allocations of various kinds of different resources, such as processor runtime, storage capacity, or network bandwidth, which are specified in the form of service level agreements (SLA). Currently, a gap exists between the capabilities of grid middleware and the underlying resource management systems concerning their support for QoS and SLA negotiation. In this paper we present an approach which closes this gap. Introducing the architecture of the virtual resource manager, we highlight its main QoS management features like run-time responsibility, co-allocation, and fault tolerance.

CoLoS - A System for Device Unaware and Position Dependent Communication Based on the Session Initiation Protocol - Lietsch, Stefan; Kao, Odej (Proc. Intelligence in Communication Systems (INTELLCOMM))

PIRANHA – Hunter of Idle Resources - Birkenheuer, Georg; Hagelweide, Wilke; Hagemeier, Björn; Japs, Viktor; Keller, Matthias; Mayr, Nikolas; Meyer, Jan; Schumacher, Tobias; Voß, Kerstin; Zajac, Markus (Proc. GI Informatiktage)

SLA-aware Job Migration in Grid Environments - Kao, Odej; Hovestadt, Matthias; Keller, Axel (Proc. Advanced Research Workshop on High Perfomance Computing: Technology and Applications)

An Architecture for SLA-aware Resource Management - Burchard, Lars-Olof; Heiss, Hans-Ulrich; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry (Proceedings of the GI-Meeting on Operating Systems)

Virtual Resource Manager: An Architecture for SLA-aware Resource Management - Burchard, Lars-Olof; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry (Proc. Int. Symposium on Cluster Computing and the Grid (CCGRID))
The next generation Grid will demand the Grid middleware to provide flexibility, transparency, and reliability. This implies the appliance of service level agreements to guarantee a negotiated level of quality of service. These requirements also affect the local resource management systems providing resources for the Grid. At this a gap between these demands and the features of today's resource management systems becomes apparent. In this paper we present an approach which closes this gap. Introducing the architecture of the virtual resource manager we highlight its main features of runtime responsibility, resource virtualization, information hiding, autonomy provision, and smooth integration of existing resource management system installations.

Efficient Querying of Transformed XML Documents - Groppe, Sven; Böttcher, Stefan; Birkenheuer, Georg (Proc. Int. Conf. on Enterprise Information Systems (ICEIS))

Using XSLT Stylesheets to Transform XPath Queries - Groppe, Sven; Böttcher, Stefan; Heckel, Reiko; Birkenheuer, Georg (Proc. East-European Conf. on Advances in Databases and Information Systems (ADBIS))

Scheduling in HPC Resource Management Systems: Queuing vs. Planning - Hovestadt, Matthias; Kao, Odej; Keller, Axel; Streit, Achim (Proc. Workshop on Job Scheduling Strategies for Parallel Processing (JSSPP))
Nearly all existing HPC systems are operated by resource management systems based on the queuing approach. With the increasing acceptance of grid middleware like Globus, new requirements for the underlying local resource management systems arise. Features like advanced reservation or quality of service are needed to implement high level functions like co-allocation. However it is difficult to realize these features with a resource management system based on the queuing concept since it considers only the present resource usage. In this paper we present an approach which closes this gap. By assigning start times to each resource request, a complete schedule is planned. Advanced reservations are now easily possible. Based on this planning approach functions like diffuse requests, automatic duration extension, or service level agreements are described. We think they are useful to increase the usability, acceptance and performance of HPC machines. In the second part of this paper we present a planning based resource management system which already covers some of the mentioned features.
Keywords: High Performance Computing; Service Level Agreement; Grid Resource; Resource Management System; Advance Reservation

Performance Evaluation, Analysis and Optimization - P. Miller, Barton; Labarta, Jesús; Schintke, Florian; Simon, Jens (Proc. European Conf. on Parallel Processing (Euro-Par))

Anatomy of a Resource Management System for HPC Clusters - Keller, Axel; Reinefeld, Alexander (Annual Review of Scalable Computing)
Workstation clusters are often not only used for high-throughput computing in time-sharing mode but also for running complex parallel jobs in space-sharing mode. This poses several difficulties to the resource management system, which must be able to reserve computing resources for exclusive use and also to determine an optimal process mapping for a given system topology. On the basis of our CCS software, we describe the anatomy of a modern resource management system. Like Codine, Condor, and LSF, CCS provides mechanisms for the user-friendly system access and management of clusters. But unlike them, CCS is targeted at the effective support of space-sharing parallel computers and even metacomputers. Among other features, CCS provides a versatile resource description facility, topology-based process mapping, pluggable schedulers, and hooks to metacomputer management.

Early Experiences with the EGrid Testbed - Gehring, Jörn; Keller, Axel; Reinefeld, Alexander; Streit, Achim (Proc. Int. Symposium on Cluster Computing and the Grid (CCGRID))
The Testbed and Applications working group of the European Grid Forum (EGrid) is actively building and experimenting with a grid infrastructure connecting several research-based supercomputing sites located in Europe. The paper reports on our first feasibility study: running a self-migrating version of the Cactus simulation code across the European grid testbed, including "live" remote data visualization and steering from different demonstration booths at Supercomputing 2000, in Dallas, TX. We report on the problems that had to be resolved for this endeavour and identify open research challenges for building production-grade grid environments.

Lessons Learned While Operating Two Large SCI Clusters - Keller, Axel; Krawinkel, Andreas (Proc. Int. Symposium on Cluster Computing and the Grid (CCGRID))
The availability of commodity high performance components for workstations and networks made it possible to build up large, PC based compute clusters at modest costs. These clusters seem to be a realistic alternative to proprietary, massively parallel systems with respect to the price/performance ratio. However, from the administration point of view, those systems are still often solely a collection of autonomous nodes, connected by a fast short area network. Therefore, aiming at providing the best possible performance in daily work to all users, a lot of work has to be done before obtaining the expected result. The paper describes the problem areas we had to cope with during the integration of two large SCI clusters (one with 64 and one with 192 processors) in the environment of the Paderborn Center for Parallel Computing.

Efficient Resource Management for Malleable Applications - Hungershöfer, Jan; Streit, Achim; Wierum, Jens-Michael